A novel nano‐size lanthanum metal–organic framework based on 5‐amino‐isophthalic acid and phenylenediamine: Photoluminescence study and sensing applications. (20th February 2019) - Sheta, Sheta M.; El‐Sheikh, Said M.; Abd‐Elzaher, Mohkles M.; Wassel, Ahmed R.
Abstract : In this paper, a novel lanthanum metal–organic framework La‐MOF was prepared via hydrothermal and reflux methods. The La‐MOF was achieved through the reaction of a 5‐amino‐isophthalic acid with 1, 2‐phenylenediamine and lanthanum chloride. The prepared La‐MOF structure was confirmed by XRD, mass spectrometry, IR, UV–Vis and elemental analysis, whereas the size, and morphology was examined by FE‐SEM/EDX and HR‐TEM. The results indicated that the La‐MOF prepared via both methods have the same structure and composition. Meanwhile, the MOF yield, reaction time, morphology, physiochemical and sensing properties were highly depended on the used preparation method. The photoluminescence (PL) study was carried out for the La‐MOF, and the results showed that La‐MOF exhibits strong emission at 558 nm after excitation at 369 nm. Moreover, the PL data indicating that the La‐MOF has highly selective sensing properties for iron (III) competing with different metal ions. The Stern‐Völmer graph shows a linear calibration curve which achieved over a concentration range 1.0–500 μM of Fe 3+ with a correlation coefficient, detection, and quantitation limits 0.998, 1.35 μM and 4.08 μM, respectively. According to the remarkable quenching of the PL intensity of La‐MOF using various concentrations of Fe 3+, it was successfully used as a sensor for Fe 3+ detecting in different water resources (pure and waste) samples. The quenching mechanism was studied and it has a dynamic type and due to efficient energy transfer between the La‐MOF and Fe 3+ . Abstract : A novel La‐MOF was synthesized and well characterized via two simple method, a unique morphology of the prepared nano‐rods and nanosheets of La‐MOF remarkably quenched by Fe 3+ and not effected by other common metal ions. The detection of fe 3+ in different water waste and pure resources is achieved. The quenching mechanism is well studied.